Botanical Gardens, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2009)
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
A picture of the well kept tropical plants and trees that are a part of the Botanical Gardens.
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Trees--Trinidad and Tobago; Plants--Trinidad and Tobago